Severity of X‐linked Dyskeratosis Congenita (DKCX) Cellular Defects Is not Directly Related to Dyskerin (DKC1) Activity in Ribosomal RNA Biogenesis or mRNA Translation. Issue 12 (21st October 2013) - Thumati, Naresh R.; Zeng, Xi‐Lei; Au, Hilda H. T.; Jang, Christopher J.; Jan, Eric; Wong, Judy M. Y.
<x xml:space="preserve">Abstract</x> Telomere attrition is the single unifying disease etiology for DKCX and HHS patients. In addition to telomere synthesis defects, we propose that other genetic or environmental modifiers can accelerate telomere attrition. Together, the effect of these factors on telomere length influences the severity of individual DKCX cases. In turn, differential telomere attrition in affected tissues alters the presentation of clinical symptoms. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>